2008
DOI: 10.1107/s1600536808038737
|View full text |Cite
|
Sign up to set email alerts
|

Aquatricarbonyl(3,5,7-tribromotropolonato)rhenium(I) methanol solvate

Abstract: Key indicators: single-crystal X-ray study; T = 100 K; mean (C-C) = 0.009 Å; R factor = 0.033; wR factor = 0.079; data-to-parameter ratio = 17.4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
15
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 12 publications
5
15
0
Order By: Relevance
“…Previous studies indicated that the substitution of the water ligands in the tri aqua species, fac-[M(CO) 3 (H 2 O) 3 ] + (M = Mn, Tc, Re) by different ligands, proceeded in three simple steps to yield predominantly mono-, di, or trisubstituted products. 5,27,28 In the current study, the monosubstitution products were confirmed by chemical and spectroscopic analysis. Similar procedures were followed and results obtained for the substitution of coordinated methanol in the rhenium analogue, fac-[Re(CO) 3 -(L,L′-Bid)(CH 3 OH)] n .…”
Section: Kinetics Of Coordinated Methanol Substitutionmentioning
confidence: 93%
“…Previous studies indicated that the substitution of the water ligands in the tri aqua species, fac-[M(CO) 3 (H 2 O) 3 ] + (M = Mn, Tc, Re) by different ligands, proceeded in three simple steps to yield predominantly mono-, di, or trisubstituted products. 5,27,28 In the current study, the monosubstitution products were confirmed by chemical and spectroscopic analysis. Similar procedures were followed and results obtained for the substitution of coordinated methanol in the rhenium analogue, fac-[Re(CO) 3 -(L,L′-Bid)(CH 3 OH)] n .…”
Section: Kinetics Of Coordinated Methanol Substitutionmentioning
confidence: 93%
“…Overall, the bond distances and bond angles around the two rhenium cores are similar to related structures and ligand systems ( [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]). When viewed along the a axis, the rhenium(I) units pack in a head-to-head fashion in column-like structures along the c axis with a slight angle to the neighbouring two units.…”
Section: Discussionmentioning
confidence: 71%
“…Although, the C-O distances of the coordinated ligand is slightly longer at 1.31 Å (1.257 Å and 1.287 Å for the uncoordinated molecule) and the C1-C2 distance is slightly shorter at 1.44 Å (1.496 Å for the uncoordinated molecule), but still within the normal range. Schutte et al synthesized the rhenium(I) tricarbonyl complexes with the tropolone and 3,5,7-tribromotropolone ligands coordinated to the metal centre [15][16][17][18]. Overall the C1-O1/C2-O2 and the C1-C2 bond distances in these structures vary from 1.276(3) Å to 1.307(8) Å and from 1.462(6) Å to 1.477(8) Å respectively.…”
Section: Discussionmentioning
confidence: 99%